Nocturnal pain in patients with rotator cuff related shoulder pain: A prospective study. (June 2022) - Mengi, Alper; Akif Guler, Mehmet
Abstract: Introduction: Nocturnal pain is a common complaint in rotator cuff related shoulder pain (RCRSP), and there is no study in literature that has evaluated the relationship between nocturnal pain severity and other evaluation parameters in RCRSP. The objective of the study was to investigate the relationship between the severity of nighttime pain and demographic and clinical data including physical examination findings, magnetic resonance imaging (MRI) findings, disability, kinesiophobia, and quality of life scores in patients diagnosed with RCRSP. Materials and methods: We assessed 61 patients (52.4% female) using the Visual Analog Scale (VAS) for nighttime and daytime, Shoulder Pain and Disability Questionnaire (SPADI), Tampa Scale of Kinesiophobia (TSK), and Short Form-36 (SF-36). Demographic and clinical data were recorded and rotator cuff specific examinations were performed and documented. RCRSP lesions were evaluated in terms of tendonitis and rupture by MRI. Results: The nighttime VAS score was positively correlated with SPADI disability and total scores, and daytime VAS score, and negatively correlated with SF-36 physical function subscale. The nighttime VAS score was associated with presence of calcific tendonitis in supraspinatus, infraspinatus tendinosis, and subscapularis tendinosis. On multivariate analysis with a linear regression model, presence of subscapularis tendinosis was an independent predictor of nighttime VAS score. In shoulder clinical tests, the nighttime VAS score correlated with only Neer test positivity. Conclusions: Our results suggest that there is a relationship between nocturnal pain severity and disability. Presence of subscapularis tendinosis appears to be a predictor of nocturnal pain severity. Additionally, patients with positive Neer test may experience more nocturnal pain. Highlights: Nocturnal pain is a common and significant problem in patients with RCRSP. Presence of subscapularis tendinosis is a predictor of nocturnal pain severity. Patients with positive Neer test may experience more nocturnal pain.